アンテイ ドウイタイ ソセイ カラ ミタ ドライバレー ノ レキシテキ ヘンセン - 中井, 信之; ナカイ, ノブユキ; 水谷, 義彦; ミズタニ, ヨシヒコ; NAKAI, Nobuyuki; MIZUTANI, Yoshihiko (国立極地研究所, 1977)
P(論文) 1973年,ドライバレーのライト谷にあるバンダ湖でDVDP 4の掘削が行われ,湖底堆積物中にgypsum, thenardite, calciteからなる層状concretionが見出された.この塩類と湖水のδ^<13>C,δ^<34>S,δ^<18>Oの測定を行い,その結果,ライト谷およびバンダ湖は過去海で,フィヨルドであったことが結論された.さらに,このことを裏付けるため,微化石の研究を行い,海綿の骨片や海洋性珪藻の破片を確認した.1975～1976年シーズンに,ドライバレーのマクマード海峡沿岸を調査し,現海水面より60～150 m高所に,厚い層状のmirabilite(またはgypsum),水,海洋堆積物が積み重なっている箇所を数ヵ所見出した.これらの安定同位体組成を測定した結果,硫酸塩鉱物と水の海洋起源を確認した.以上のように,過去海水面が現在より150mも高い時代のあったことが明らかになり,ドライバレーの中で標高95m以上のライト谷やバンダ湖,その他テイラー谷も,過去海底であった時代があったといえる. In 1973, DVDP 4 drilling was performed to obtain unconsolidated sediments of Lake Vanda, McMurdo Oasis. The cored sediments were found to contain layered salt concretions composed of gypsum, thenardite and calcite. On the basis of stable isotope compositions, δ^<13>C, δ^<18>O and δ^<34>S, on the water and salts, it was concluded that the lake and the Wright Valley were once a fijord containing sea water and isolated from the ocean by glaciation. Micropaleontological studies for the cored sediments were also performed, indicating the existence of marine fossil fragments, marine sponge microsclere and marine centric diatom, only below the 1st gravel laver. This supports the above conclusions. In the 1975-1976 field survey season, layered mirabilite (or gypsum), ice and marine sediment, which were found under moraines at the height of 60 to 150 m above sea level near the coast of McMurdo Sound, have been studied on their occurrences and analyzed isotopically. These sulfate minerals and ice were found to be of marine in origin according to their isotopic compositions. This fact suggests that the sea water level largely fluctuated in geologic time and reached possibly 150 m higher than the present, and the present Wright Valley and Taylor Valley were under ocean water in the past. departmental bulletin paper